The Application of Progressive Muscle Relaxation Therapy on Changes in Blood Pressure in Elderly with Hypertension - Paramita Ratna Gayatri; Sheylla Septina Margaretta; Wahyu Nur Pratiwi (STIKES Adi Husada, 2023)
High blood pressure is one of the most common non-communicable diseases suffered by the elderly. The changes in the cardiovascular system due to increasing age are the cause of hypertension in the elderly which may caused many complications if not controlled properly. High blood pressure can be treated with pharmacological and non-pharmacological therapy. One of the non-pharmacological therapies that can be given to hypertension sufferers is progressive muscle relaxation therapy.This research aims to determine wether there is alteration in elderly people’s blood pressure after The Progressive Muscel Relaxation Therapy applied. This research was a quasi experimental research with two group which is Intervention Group and Control Group. There were 31 elderly people with hypertension in each who met the suitables criteria. The results of the study showed variations in the blood pressure of respondents in the intervention group and control group before and after being given progressive muscle therapy at meetings 1 to 6. It was found that blood pressure in the intervention group was reduced. The results of the Independent T-test statistical test showed a significant ρ-value of 0.000 where ρ < α (α : 0.05), which means that providing progressive muscle relaxation therapy has an effect on changes in blood pressure in elderly people with hypertension. The research concluded that there was an effect of applying progressive muscle relaxation therapy on changes in blood pressure in elderly people with hypertension.